El Derecho como medio de control de las barras bravas: ¿hacia un futbol en paz? (2021)
The purpose of this article is to study the legal relationship between the so-called "Barras bravas" and the Colombian State. To do so, it will first describe the emergence of this phenomenon in England with the Hooligans and its expansion throughout the world, especially in Latin America where the phenomenon is usually presented as an immediate problem to be intervened by the state institutions of each country, with special emphasis on Colombia. Afterwards, the main norms that exist in Colombia that regulate the soccer issue will be identified, and a small dogmatic and doctrinal analysis of their articles will be made. In the third chapter there is a study of how these regulations described in the previous chapter are applied in the Colombian reality, of which have been the shortcomings, but also the successes that have been had from the institutionality to form a soccer culture in peace. Finally, a series of conclusions are drawn.